Perceived Government Support on MSME Business Performance: The Mediating Role of Digital Capability - Aryani Aryani; Muh. Syahru Ramadhan; Fahrul Mauzu (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to examine how perceived government support affects MSME performance, mediated by digital capability in Dompu Regency. Research Method: A quantitative approach was used, involving a survey of 100 MSME actors selected through purposive sampling. Primary data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. Results and Discussion: The PLS-SEM analysis indicates that perceived government support significantly enhances both MSME performance and digital capability. Furthermore, digital capability positively affects performance and significantly mediates the relationship between government support and MSME performance. This demonstrates that external government support requires internal digital internalization to optimize business results. Implications: Theoretically, it extends the Resource-Based View by positioning digital capability as a strategic mechanism. Practically, it urges local policymakers to integrate digital competency training into MSME empowerment programs. Future studies should expand geographically and explore other moderating factors. Originality: This research uniquely positions digital capability as a mediator rather than an independent variable in a non-metropolitan context characterized by distinct gaps in digital infrastructure.